Mr. Putter & Tabby drop the ball - Rylant, Cynthia (Harcourt Children's Books, Houghton Mifflin Harcourt, 2013)
Mr. Putter and his cat Tabby take time off from napping to play on the Yankee Doodle Dandies baseball team.